The Effect Of Levarage, Legislative Measures, Intergovernmental Revenue And Regional Tax Revenue On Regency/City Government Financial In Indonesia - Indi Aprianto (TRIGIN PUBLISHER, 2021)
This study aims to determine the effect of leverage, the size of the legislative, intergovernmental revenue and local tax revenues to financial performance of districts/cities in Indonesia. The analysis models is the multiple linear regression analysis. The sample in this study are 45 districts/cities in Indonesia. The type of the data in this research is secondary data. The sampling method is a purposive sampling method. And the data processing using SPSS. The results contained in this research is the size of the legislature and local tax revenue is partially significant effect on the financial performance of districts/cities in Indonesia. And other result is leverage, the size of the legislative, intergovernmental revenue and local tax revenues together has a significant effect on the financial performance of districts/cities in Indonesia.